Thermodynamic Study of Plant Growth in Nature Part-II Method of Calculating Productive Capacity of Site - Bose, K. J. C. (Indian Forester, 1973)
Potential productivity of forest was hitherto studied in emperical way. Plant growth is a bio-chemical process and same raw material is used by all the species for vegetative growth. Application of law of mass action to this chemical process taking into account environmental factors of plant growth like climate, soil moisture and physiological characters of plant community, it is possible to derive a formula for calculating productivity of site. Applicability of this new formula is tested case of sal forests of Dehra Dun and Gorakhpur regions and C.A.I. for these regions is calculated. It agrees with the actual C.A.I. of sal forests of these zones. The fast growth of eucalyptus and grass land formation in the climatic zone of moist deciduous forest Is explained through the same formula.